Investigate the factors related to the intention to perform physical activity based on the theory of ‎planned behavior among high school female students of Ahvaz city - Zahra Baji; Ghodratollah Shakerinejad; Masoumeh Tehrani; Saeedeh Hajinajaf; Farzaneh Jarvandi (Hamadan University of Medical Sciences, 2017)
Background and Objectives: Exercise and physical activity are important health behaviors for preventing disease and mortality and positive relationship with physical and mental health promotion. The purpose of this study was to investigate the factors related to the intention to perform physical activity based on the theory of planned behavior among high school female students of Ahvaz city in 2016-2017. Materials and Methods: This cross-sectional study was performed on 163 high school female students who were randomly selected from public schools in Ahvaz city. Data were gathered using questionnaire include demographic characteristics (5 items) And the theory of planned behavior structure including attitude (9 items), subjective norms (6 items), perceived behavior control (4 items) and intention (4 items). Finally, data collected and analyzed by SPSS software version 23 using regression analysis and Pierson correlation coefficient. Results: The mean age of participant's was 13.76±0.89. In regression model, the attitude (β=0.46, p<0.001) and perceived behavior control (β=0.15, p<0.05) were predictors of the physical activity intention. This model could explain 40% of the variance of the physical activity intention. Among these variables, the effect of attitude was greater than other variables (P<0.001, β=0.46). Conclusion: The results showed that attitude and perceived behavioral control were predictors of physical activity behavior intent. The results reveal the perceived behavior control, attitudes and subjective norms could predict physical activity intention. Therefore, using this theory and paying more attention to the attitude structure is important as the strongest predictor of behavior It is important to target intent and promotion of physical activity behavior in this group.